Lymph nodes can accurately be measured on PET-CT for lymphoma staging/restaging without a concomitant contrast enhanced CT scan. Issue 5 (3rd May 2016) - Simpson, William L.; Lee, Karen M.; Sosa, Ninoska; Cooper, Nancy; Scigliano, Eileen; Brody, Joshua D.; Doucette, John T.; Kostakoglu, Lale
Abstract: Dual imaging with both contrast enhanced CT scan and PET-CT is recommended for evaluation of lymphoma. We compared the performance in identification and size measurements of involved lymph nodes in FDG-avid lymphomas on the low dose non-contrast enhanced CT of a PET-CT scan with those on a diagnostic contrast enhanced CT scan. The size of FDG-avid lymph nodes was measured in both the short and long axis on both the low dose non-contrast CT of the PET-CT and the contrast enhanced CT by two independent readers. A total of 307 FGD avid lymph nodes were identified in 52 patients. There was no statistically significant differences in the measured size of the nodes on the non-contrast and contrast enhanced scans ( p = 0.21). Baseline staging and restaging of FDG-avid lymphomas can be performed with one test, PET-CT, without an accompanying contrast enhanced CT scan, with no effect on the measured nodal size.